Plano de negócio para a empresa Berimbau Estúdio: produtora de música e sonorização de filmes - Biancolini, Lucas Mompean (Universidade Federal de São Carlos, 2025)
Music is a universal form of art that connects people and emotions, and Berimbau Estúdio stands out in this context as a space dedicated to audio creation and production. Each note, chord, and word is carefully crafted to convey emotion, tell stories, and impact the audience. However, for this art to also become a prosperous and sustainable business, it is essential to rely on a solid and strategic business plan. This final graduation project aims not only to fulfill an academic requirement but also to significantly contribute to the development and growth of Berimbau Estúdio. The business plan will be replicated within the company to achieve common goals between the student and other team members. The main objective is to develop a business plan for Berimbau Estúdio that serves as a guidance and management tool for the company, encompassing a comprehensive analysis of the business, focusing on the implementation of a project management flow and promoting collaboration across all areas of the business. It will be a guide that gathers information about the characteristics, conditions, and future needs of the business, aiming to analyze its potential, feasibility, and facilitate the implementation of new strategies. The research was conducted using both quantitative (numerical data) and qualitative (collection of strategic company content) methodologies as part of a case study, including experiences with the team, document analysis, and financial data. The results achieved include the implementation of an efficient management system ("Sortd" platform for demand distribution in production) and an economic feasibility analysis, with the potential to expand commercial strategies. It is concluded that the practical application of the knowledge acquired during the course can significantly contribute to the company in sales strategies as well as in workflow management.
Business plan for Berimbau Studio: music production and film sound design company
Keywords: Produção de áudio; Estratégia empresarial; Gestão integrada; Sustentabilidade financeira; Empreendedorismo; Mercado audiovisual; Audio production; Business strategy; Integrated management; Financial sustainability; Entrepreneurship; Audiovisual market; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO FINANCEIRA